Effects of Fe and Zn on growth, biofortification and quality of lettuce grown in hydroponics - da Silva, Vitor B. [UNESP]; Ribera, Laura M. [UNESP]; Medelo, Maria J. Y. [UNESP]; de Almeida, Hilário J. [UNESP]; Filho, Arthur B. Cecílio [UNESP] (FapUNIFESP (SciELO), 2024)
Iron (Fe) and zinc (Zn) are essential elements for human health and their deficiencies cause reduced work capacity, physiological and immune system disorders, anemia and even death, being considered primary global public health problems. Agronomic biofortification aims to increase the concentration of these nutrients in the edible part of the plant and, consequently, increase human intake of these nutrients. The aim of this study was to evaluate the effects of Fe and Zn concentrations on the growth, biofortification and quality of lettuce grown in hydroponics. Six treatments corresponding to the combinations of Zn (0.06 and 0.24 mg L-1) and Fe (2, 4 and 8 mg L-1) concentrations were evaluated. Increase of Zn in the nutrient solution positively influenced only leaf Zn contents at 18 days after transplanting the seedlings and ascorbic acid at harvest. On the other hand, the increase in Fe concentration positively influenced the contents of photosynthetic pigments, ascorbic acid and Fe; however, it negatively affected the leaf Zn content, leaf area and leaf dry mass of lettuce. Greater biofortification of lettuce for Fe was observed with the Fe concentration of 8 mg L-1 in the solution.
Efeitos do Fe e Zn no crescimento, bioforticação e qualidade de alface cultivado em hidroponia
Keywords: Biofortified food; Hidden hunger; Lactuca sativa L; Nutrient deficiency; Soilless cultivation